Features of the formation of communication activity of hearing-impaired students in the process of joint art-felting training - Абдуллина, Куралай; Жиенбаева, Надежда (Pedagogy and Psychology, 2021)
The article considers the features of the formation of meaningful components of communication of hearing-impaired students of grades 5-7 in the conditions of joint training in the national applied art -felting. The methods of social activity of students based on the formation of creative knowledge and correction of physical state by means of art felt are described. The main idea of the education of hard-of-hearing students is the preservation of residual auditory qualities, an increase in vocabulary in the development of independent communication skills, the ways of providing special psychological and pedagogical support in the process of teaching and upbringing, through the art of national felting, are described. The specific of the art - felting process as an effective joint activity of children with hearing impairments is substantiated. Experimentally revealed: features of the formation of speech communication of hearing-impaired students in the subject-practical classes "Artistic work"; the importance of national art - felting in the activation of speech and cognitive joint activity of students. The results of compensatory capabilities of students with hearing impairments in the process of learning the national applied art – felting are demonstrated.